Water Quality of Batang Ai Reservoir And its inflow (Engkari River) - Siti Maisarah, Binti Abd Rahim (Universiti Malaysia Sarawak, UNIMAS, 2013)
Water quality of river and reservoir is important to be monitored so that it is not harmful to both human and environment. For Batang Ai Reservoir, it is used for aquaculture purpose which could affect the water bodies there. Engkari River also needs to be monitored as it is one of the main inflows of the reservoir. Therefore, the objectives of this study were to evaluate the impact of aquaculture on the water quality of Batang Ai Reservoir and determine the water quality of Engkari River. Five sampling stations were selected consisting of inflow area, reservoir and near outflow of reservoir where water sample was taken at sub-surface and bottom of the river. The range of results for the waterquality parameters were TSS (1.67 – 37.63 mg/L), BOD5 (2.4 – 7.53 mg/L), NitriteN (0.0113 – 0.0158 mg/L), TP (25.59 - 1140.41 µg/L) and TKN (0.4841 – 2.289 mg/L). Most of the higher readings came from the bottom of the station near the aquaculture and residential area. Conductivity ranged from 19 – 66 µS/cm and was higher at bottom compared to the sub-surface. The highest concentration of heavy metals detected was zinc with the range of 0.014 – 0.191 mg/L.